Implementation of the Quality of Financial Information and its Impact on the Performance of MSMEs in Bandar Lampung - Nurhayati Widi Utami; Sudrajat Sudrajat (International Journal of Economics Development Research (IJEDR), 2023)
MSMEs are recognized as a sector that drives economic growth. However, MSMEs often face challenges in financial management, including the accurate and reliable preparation of financial reports. Based on research activities, it was found that 75% of MSMEs do not regularly manage and present financial information. This is attributed to several issues faced by MSMEs. The primary problem identified is the limitation of competent human resources. The majority of MSMEs lack adequate financial experts. Additionally, some MSMEs also encounter issues such as a lack of understanding of proper financial information recording for appropriate business decision-making. However, the current trend of using digital payment QRIS is considered very high and continuously increasing, driven by the role of QRIS in providing benefits to merchants, including MSMEs. This research was conducted on MSMEs located in Bandar Lampung and aimed to analyze the role of QRIS in driving MSME performance in the context of enhancing the quality of financial information. The purposive sampling technique was utilized for sampling. A questionnaire was used as a research tool, employing Structural Equation Model (SEM) as the data analysis technique, including outer model and inner model testing. The research results indicate that the quality of financial information, as an intervening variable, can indirectly influence the improvement of MSME performance following the implementation of QRIS in the digital payment.